State Aid in the European Union: Where Law and Economics Meet Together (Global Journal of Human-Social Science, 2021)
The main aim of this article is to give an overview about the Competition Law of the European Union with special regard to the provisions on State Aid which basically determine the level playing field a Member State can grant subsidies for enterprises primarily for economic purposes. Besides the legal environment by giving a brief theoretical summary on the need for State intervention I gave some contributions about the empirics of State aid by analysing the State aid expenditure, economic growth and income level in the European Union between 2004 and 2019.
Keywords: European Union; Competition Law; State aid; economic growth; income level